First report of a South American short-faced bears' den (Arctotherium angustidens): palaeobiological and palaeoecological implications - Soibelzon, Leopoldo Héctor (2009)
Here we report the first example of associated short-faced bear fossils from South America. The specimens represent three individuals referable to the Ensenadan (early to middle Pleistocene) species Arctotherium angustidens (Ursidae, Tremarctinae), the giant South American short-faced bear. Although the fossil record of short-faced bears in South America is very rich, they have not previously been recorded in association. These three individuals were found in a cave during quarry exploitation. We suggest that these bears represent the first record of a family group and open the discussion about cave utilization and hibernation or torpor by South American short-faced bears.